2018
DOI: 10.1103/physreve.97.032102
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport in oscillator chains with long-range interactions coupled to thermal reservoirs

Abstract: We investigate thermal conduction in arrays of long-range interacting rotors and Fermi-Pasta-Ulam (FPU) oscillators coupled to two reservoirs at different temperatures. The strength of the interaction between two lattice sites decays as a power α of the inverse of their distance. We point out the necessity of distinguishing between energy flows towards or from the reservoirs and those within the system. We show that energy flow between the reservoirs occurs via a direct transfer induced by long-range couplings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…3 changes geometry. We show in the inset of cous heat equations predict a steeper-than-Fourier's law or non-linear temperature gradient that is reminiscent of that obtained in molecular dynamics simulations [88][89][90][91][92][93][94][95][96][97] and in explicit solutions of the LBTE [34].…”
Section: Case Studysupporting
confidence: 59%
“…3 changes geometry. We show in the inset of cous heat equations predict a steeper-than-Fourier's law or non-linear temperature gradient that is reminiscent of that obtained in molecular dynamics simulations [88][89][90][91][92][93][94][95][96][97] and in explicit solutions of the LBTE [34].…”
Section: Case Studysupporting
confidence: 59%
“…These include dipolar BECs [50], where the recent formation of quantum droplets and their bound states [51] suggests that interesting types of long-range interactions can also arise in the study of BECs in optical lattices. Long-range interactions also play important roles in the study of coupled phase oscillators in diverse physical settings [26], heat transport in oscillator chains coupled to thermal reservoirs [52,53], and more. (1) with frequency f b ≈5.…”
Section: Discussionmentioning
confidence: 99%
“…In Refs. [20][21][22], the coupled rotor model was studied. This model shows a transition from the diffusive transport to the thermal insulator, as δ decreases from infinity.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23], the Fermi-Pasta-Ulam (FPU) model was investigated, and it was found that the transport behavior is generally anomalous, except at δ = 2, where it exhibits ballistic behavior [23]. In stud-arXiv:1906.08457v1 [cond-mat.stat-mech] 20 Jun 2019 ies on the FPU model, long-range interactions can be added in several ways, e.g., long-range quadratic potential terms [24], long-range quartic potential terms [13,23], and a combination of both [8,22]. From these studies, many intriguing transport properties have been numerically shown.…”
Section: Introductionmentioning
confidence: 99%